2021
DOI: 10.1038/s42255-021-00380-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining the lineage of thermogenic perivascular adipose tissue

Abstract: Brown adipose tissue can expend large amounts of energy, and therefore increasing its size or activity is a promising therapeutic approach to combat metabolic disease. In humans, major deposits of brown fat cells are found intimately associated with large blood vessels, corresponding to perivascular adipose tissue (PVAT). However, the cellular origins of PVAT are poorly understood. Here, we determine the identity of perivascular adipocyte progenitors in mice and humans. In mice, thoracic PVAT develops from a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…Discrete thermogenic pathways could segregate inter-or intracellularly. The identi cation of distinct adipocyte subtypes [51][52][53][54][55][56] as well as mitochondrial heterogeneity within thermogenic fat cells 57 supports this idea. Thus, the futile creatine cycle probably operates in conjunction with UCP1-dependent thermogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…Discrete thermogenic pathways could segregate inter-or intracellularly. The identi cation of distinct adipocyte subtypes [51][52][53][54][55][56] as well as mitochondrial heterogeneity within thermogenic fat cells 57 supports this idea. Thus, the futile creatine cycle probably operates in conjunction with UCP1-dependent thermogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…Single-cell techniques have empowered this process by helping draw sophisticated cellular atlas. Some researchers have explored the heterogeneity of PVAT at a single-cell level and uncovered distinct clusters with specific signature markers and signaling pathways ( Angueira et al, 2021 ). Creating a more precise map of such a complex tissue from single-cell sequencing data is, therefore, a challenging task, which on the other hand, opens an opportunity for us to dive into this unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A lineage-tracing study further elaborates that anterior tPVAT adipocytes can be traced to SM22α + progenitors, whereas left lateral tPVAT presents both SM22α + and Myf5 + features (Ye et al, 2019). However, recent cell differentiation assays and genetic fate mapping studies show that fibroblastic progenitor cells but not vascular smooth muscle cells (VSMCs) are responsible for tPVAT adipogenesis (Angueira et al, 2021), which contradicts the previous findings (Chang et al, 2012;Ye et al, 2019). Progenitor cells for tPVAT are from a fibroblastic lineage, including (Pdgfra + ; Ly6a + ; Pparg − ) and preadipocytes (Pdgfra + ; Ly6a − ; Pparg + ).…”
Section: Origin Of Thoracic Periaortic Adipose Tissuementioning
confidence: 97%
See 1 more Smart Citation
“…More importantly, CD81 + cells respond to the cold challenge by giving rise to new brite/beige positive adipocytes in the inguinal adipose tissue, while the loss of CD81 causes diet-induced obesity and other complications [ 26 ]. In the newest study, Angueira et al reported three brown adipogenic populations by applying scRNAseq and linage tracing to perivascular adipose tissue, comprising progenitors (Pdgfra + ; Ly6a + ; Pparg-), preadipocytes (Pdgfra + ; Ly6a-; Pparg +) [ 27 ], and a novel subpopulation of smooth muscle cells (Myh11 + ; Pdgfra − ; Pparg +) within the aortic adventitia of adult mice. These three populations of cells possess the capacity to generate adipocytes in vitro and in vivo and give rise to brown adipocytes in perivascular adipose tissue.…”
Section: Heterogeneity Of Vascular Mural Apcsmentioning
confidence: 99%